Valuation- non tender for bracing redesign & related work - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC Joint Venture for valuation- non tender for bracing redesign & related work of Brac University new campus project.